2021
DOI: 10.1186/s12889-021-10587-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the timely uptake of initial HIV virologic test among HIV-exposed infants attending clinics within a faith-based HIV program in Kenya; a cross-sectional study

Abstract: Background Early infant diagnosis (EID) of HIV, followed by effective care including antiretroviral therapy (ART), reduces infant mortality by 76% and HIV progression by 75%. In 2015, 50% of 1.2 million HIV-exposed infants (HEI) in 21 priority countries received a virologic test within the recommended 2 months of birth. We sought to identify factors associated with timely uptake of virologic EID among HEI and gain insight into missed opportunities. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Mothers delivering at home do not have access to these services, resulting in delays in the early diagnosis of the serostatus of the infant and subsequent non-enrollment in care and treatment services. [ 28 ] Further analyses in our study indicated that home delivery was not significantly correlated with children’s enrollment in treatment and care. These findings suggest that regardless of the place of birth, child ART services are available and accessible despite the place of birth.…”
Section: Discussionmentioning
confidence: 66%
“…Mothers delivering at home do not have access to these services, resulting in delays in the early diagnosis of the serostatus of the infant and subsequent non-enrollment in care and treatment services. [ 28 ] Further analyses in our study indicated that home delivery was not significantly correlated with children’s enrollment in treatment and care. These findings suggest that regardless of the place of birth, child ART services are available and accessible despite the place of birth.…”
Section: Discussionmentioning
confidence: 66%
“…The studies published between January 2012 and March 2022 were carried out in a range of East African countries; namely, Burundi [ 57 ], Comoros [ 57 ], Ethiopia [ 25 , 45 , 57 74 ], Kenya [ 57 , 75 78 ], Malawi [ 25 , 45 , 57 74 , 79 ], Mozambique [ 57 , 76 78 , 80 ], Rwanda [ 57 ], South Sudan [ 81 ], Tanzania [ 82 , 83 ], Uganda [ 39 , 57 , 84 87 ], Zambia [ 57 , 88 90 ], and Zimbabwe [ 57 , 91 96 ]. Studies conducted among eligible pregnant/postpartum women, infants and service providers were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, women who had symptoms of sexually transmitted infections [ 95 ] and more ANC visits [ 64 , 65 , 95 ] were found to be more likely to use the HIV test service. Women who were on ART during pregnancy or at the time of the HIV PCR test and infants who had ARV prophylaxis at birth were positively associated with EID [ 45 , 76 ]. Likewise, factors such as ANC follow-up [ 62 ], birth at a government health facility [ 45 ], and maternal ART adherence [ 89 ] were found to be positively correlated with EID.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, independent predictive factors for a lack of EID were not clearly identified. Other studies have investigated on this topic: lack of maternal ART or infant prophylaxis, [17][18][19] lack of maternal ANC attendance, 20,21 new maternal HIV diagnosis, 18 lack of information about the importance of early testing 22 have all been identified as possible predictors of the lack of an EID. In one study in rural Malawi (2013-2016) it was also shown that receiving an infant HIV test result was associated to a reduced infant study retention, especially an infant's positive result.…”
Section: Discussionmentioning
confidence: 99%